Systemic lupus erythematosus in Sarawak General Hospital: A 10-year update - Sharifah Aishah, Wan; Teh Cheng Lay, Teh; Cheong, Yaw Kiet; Chuah, Seow Lin; Sachdev, Benjamin Manjit Singh; Ahmad Tirmizi, Jobli (John Wiley & Sons, Inc., 2024)
Background/Purpose: Systemic lupus erythematosus (SLE) is a complex autoimmune disease with heterogeneous clinical presentation. We published the Sarawak Lupus Cohort in 2014. Since then there have been many advances in SLE diagnosis and management. We aimed to examine the clinical manifestations and gender differences of an updated SLE cohort in Sarawak General Hospital. Methods: We collected demographics and clinical manifestation data in this prospective observational study from July 2018 until December 2023. All patients fulfilled the 2012 Systemic Lupus Collaborating Clinics (SLICC) Classification Criteria for SLE. Statistical analysis was performed using SPSS, with means ± SD, Chi-Square or Fisher's exact test. A p-value<0.05 is considered significant. Results: There were 637 patients in our cohort, with 567 (89%) women and 70 (11%) men. The mean age at SLE diagnosis was 31.17 ± 13.6 years. There were 234 (36.7%) Chinese, 224 (35.2%) Malay, 107 (16.8%) Iban, and 58 (9.1%) Bidayuh patients. Common SLE clinical manifestations were acute cutaneous lupus in 420 (65.9%), followed by renal in 309 (48.5%) and leucopenia or lymphopenia in 307 (48.2%) patients. The common immunological SLE manifestations were antinuclear antibody (ANA) in 619 (97.2%) and anti-double stranded DNA (anti-dsDNA) in 366 (57.5%) patients. 285 (44.7%) patients had severe disease at presentation. There were 217 (34.1%) patients with a score of SLE Damage Index (SDI) >1, indicating the presence of at least one item of damage. There were 70 (11%) deaths in this cohort. The notable differences between men and women with SLE was a statistically significant higher percentage of men had renal manifestation (men 41 (58.6%) vs women 268 (47.3%), p = 0.04) and serositis (men 18 (25.7%) vs women 91 (16.0%), p = 0.04). There were more women than men with oral ulcers (women 220 (38.8%) vs men 15 (21.4%), p = 0.004) and alopecia (women 278 (49.0%) vs men 13 (18.6%), p < 0.001). More men had severe disease at presentation (men 42 (60%) vs women 243 (42.9%), p = 0.006). Among patients with SDI>1 (n = 217), there were more men with end-stage renal failure (ESRF) (men 7 (28%) vs women 11 (5.7%), p = 0.002), myocardial infarction (men 2 (8%) vs women (0), p = 0.01) and extensive skin scarring (men 3 (12%) vs women 4 (2.1%), p = 0.04). There was no gender difference in death in this cohort. Conclusion: This updated SLE cohort showed acute cutaneous lupus, renal, ANA and anti-dsDNA as the most common SLE manifestations. Men had more severe disease at presentation, with more renal and serositis SLE manifestation. Men had more ESRF, myocardial infarction and extensive skin scarring in the SLE Damage Index.